Changes in Cyclic Chemical Elements in Saline Landscape - Yuldashev G; Azimov Z; Mamajonov I (Zien Journals, 2023)
In Central Fergana, over 50 years, in non-irrigated primary solonchaks, the degree of salinity practically did not increase; it remained within 2.5-3% of the dry residue, and the concentration of salts in groundwater did not increase, which was facilitated by wind erosion, the construction of collector-drainage networks in the adjacent territory. The level of content of macro- and microelements of the group of cyclic elements in soils of relatively autonomous landscapes with a developed solonchak profile on the surface in a layer with a thickness of 0-3 cm is quite high, in addition, water-soluble salts are contained in an amount of more than 3%. As for Clarke, the concentrations of Na-3.9, K-0.81, Ca-2.60, Fe-0.69, Ba-1.28, and the content of trace elements vary within 0.71-5.69.
Keywords: Clarke concentration; microelements; accumulation; secondary solonchaks